Method for preparing high-entropy spinel type oxide material by using microwave hydrothermal method as well as product and application of high-entropy spinel type oxide material
The preparation of high-entropy spinel oxide materials by microwave hydrothermal method solves the problems of uniform distribution and morphology control of multi-components in traditional methods, and achieves efficient and uniform synthesis, which significantly improves the performance and environmental protection of the material.
Patent Information
- Application Number
- CN202411573077.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The preparation of high-entropy spinel oxide materials faces the challenge of multi-component uniform distribution and stable crystal structure. The traditional hydrothermal method is complex in operation, has a long reaction time, is difficult to control the morphology and particle size distribution, and has environmental pollution problems.
Using microwave hydrothermal method, the metal sources of iron, cobalt, nickel, chromium, zinc and copper are dissolved in water. After adding precipitant, microwave hydrothermal, cooling, washing, centrifugation, drying and calcining are performed to accurately control the shape of the product. Profile and particle size distribution.
It achieves efficient and uniform distribution of metal elements, significantly accelerates the reaction speed, accurately controls the morphology and particle size distribution of the material, reduces energy consumption and environmental pollution, and improves the catalytic activity, electrochemical performance and stability of the material.
Smart Images

Figure CN119430311A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material science and chemical engineering, and in particular relates to a method for preparing a high-entropy spinel oxide material by using microwave hydrothermal method, and a product and application thereof. Background Art
[0002] High entropy oxides, as an innovative new material, were first proposed in 2015 by a team of scientists including Rost, Maria and Curtarolo, and published groundbreaking research results. Due to its unique multi-principal element characteristics and disordered arrangement between principal elements, this material is easy to form a variety of solid solution structures such as rock salt, calcium fluoride, spinel or perovskite, thereby showing excellent performance. Especially in the field of energy storage and magnetic materials, high entropy oxides show great application potential. There are various preparation methods for high entropy oxides, including solid phase method, pyrolysis method, coprecipitation method, hydrothermal synthesis method and liquid phase combustion synthesis method. These methods have their own advantages and provide rich choices for the research and application of materials. Compared with traditional oxides, high entropy oxides have many significant advantages, such as rich active sites, adjustable specific surface area, stable crystal structure, and unique geometric compatibility and electronic structure characteristics. These characteristics make their importance in the field of materials science increasingly prominent. In particular, high entropy spinel oxides have shown excellent performance in the application of energy storage and magnetic materials, making them ideal oxide materials and attracting much attention from the scientific research community and industry.
[0003] However, due to its complex crystal structure and multi-component characteristics, the preparation of high-entropy spinel oxide materials still faces some challenges and problems, mainly including the following aspects:
[0004] 1. High-entropy spinel oxide materials are multi-element alloys composed of multiple metal elements. How to achieve uniform distribution of each component and form a stable crystal structure is a challenge;
[0005] 2. The traditional hydrothermal method has complicated operation steps, long reaction time, and the morphology and particle size distribution of the prepared product are uncontrollable;
[0006] 3. Due to the multi-component characteristics of high-entropy spinel oxide materials, their performance is often affected by the content of each component, and different synthesis conditions will also affect their performance, so the preparation process needs to be finely controlled;
[0007] 4. The traditional hydrothermal method for preparing high-entropy spinel oxide materials will produce a large amount of waste liquid and waste gas, causing certain pollution to the environment.
[0008] Therefore, there is an urgent need to provide a method that is simple and easy to implement and can accurately control the morphology and particle size distribution of high-entropy spinel oxide materials. Summary of the invention
[0009] In view of the above technical problems, the present invention proposes a method for preparing high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method and its products and applications.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] One of the technical solutions of the present invention:
[0012] A method for preparing a high entropy spinel oxide material by microwave hydrothermal treatment comprises the following steps:
[0013] Dissolve six metal sources, namely iron, cobalt, nickel, chromium, zinc and copper, in water in equal moles of metal ions, and stir evenly to obtain a mixed solution;
[0014] A precipitant is added to the mixed solution, and then microwave hydrothermal, cooling, washing, centrifugation, drying and calcination are performed in sequence to obtain a high entropy spinel oxide material (FeCoNiCrZnCu)3O4.
[0015] Beneficial effects: The present invention adopts microwave hydrothermal to prepare high entropy spinel oxide materials, cleverly uses microwave energy to supplement the temperature deficiencies of traditional hydrothermal methods, and greatly improves the efficiency of practical applications. That is, the microwave hydrothermal method can quickly reach high temperature and high pressure reaction conditions with its higher heating efficiency and uniformity, and significantly accelerate the reaction rate. At the same time, the technology can also more accurately control the morphology and particle size distribution of the product during the synthesis process, providing a powerful means for preparing high-quality functional materials. Among them, the present application selects six metal ions of iron, cobalt, nickel, chromium, zinc and copper and prepares oxide materials in an equimolar ratio in order to accurately control the morphology, composition and oxidation state of the material by substitution of uniformly distributed metal ions in the lattice, thereby obtaining a multi-element oxide with optimized structure and performance. The equimolar ratio of these metal ions can ensure the formation of a stable spinel or similar structure, provide abundant active sites, enhance electron transport performance, and enhance the overall catalytic activity, electrochemical performance and stability of the material through the synergistic effect between metal ions, so that it can show excellent performance in related applications.
[0016] Preferably, the metal source is a hydrated metal nitrate.
[0017] Preferably, the six metal sources of iron, cobalt, nickel, chromium, zinc and copper are respectively: Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cr(NO3)2·9H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O.
[0018] Preferably, in the mixed solution, the concentration of each metal ion is 0.01-0.06 mol / L.
[0019] Preferably, the precipitant comprises one or two of disodium ethylenediaminetetraacetate, ammonium fluoride, glucose, ammonia water or urea.
[0020] Preferably, the molar ratio of the precipitant to the total metal ions in the mixed solution is: (3-6):1.
[0021] Preferably, the parameter conditions in the microwave hydrothermal process are:
[0022] The rated output power of the microwave is 400W, the microwave operating frequency is 2450MHz, the microwave hydrothermal temperature is 100-160℃, and the insulation time is 0.5-6h.
[0023] Preferably, the washing process comprises the following specific steps:
[0024] The precipitate obtained by cooling was washed three times with ethanol and deionized water in turn.
[0025] Preferably, the parameter conditions during the centrifugation process are:
[0026] Centrifuge at 8000 rpm for 3 min.
[0027] Preferably, the drying process is: drying at 60° C. for 10 hours.
[0028] Preferably, the calcination process is:
[0029] The temperature is raised to 300-900°C at a heating rate of 2-10°C / min, and then maintained at this temperature for 0.5-5h.
[0030] The second technical solution of the present invention:
[0031] A high entropy spinel oxide material is prepared by the above method.
[0032] Preferably, the high entropy spinel oxide material has a morphology of round nanoparticles, a porosity of 0.074 to 0.253 cc / g, a particle size of 3.062 to 3.414 nm, and a specific surface area of 27.017 to 168.271 m 2 / g.
[0033] The third technical solution of the present invention:
[0034] Application of the above-mentioned high entropy spinel oxide material in the field of catalytic water electrolysis.
[0035] Compared with the prior art, the present invention has the following advantages and technical effects:
[0036] 1. The present invention uses metal nitrate as raw material, which is low in cost, easy to handle and has a wide range of sources;
[0037] 2. The present invention utilizes microwave hydrothermal method to accurately prepare raw materials in a liquid environment, thereby ensuring uniform distribution of metal elements and making the product accurately match the predetermined stoichiometric ratio. This method not only has mild reaction conditions, energy-saving and high efficiency, and cost-effectiveness, but also the entire synthesis process is green and environmentally friendly;
[0038] 3. The high-entropy spinel oxide material prepared by the method of the present invention exhibits excellent catalytic activity, stability and corrosion resistance in electrocatalysis, effectively improving the efficiency and life of the electrocatalytic reaction.
[0039] The microwave hydrothermal method of the present invention prepares high entropy oxides. By comparing with the existing patented technology, it reveals its innovation in the reaction principle, that is, the unique synergistic effect of microwave hydrothermal is used to effectively overcome the difficulties of high reaction temperature, high energy consumption, uneven element distribution, and the prejudice against uniform solid solution of complex components in the existing technology. The present invention realizes the rapid synthesis of high entropy oxides with high uniformity and crystallinity at a relatively low temperature, which not only greatly improves the catalytic performance and electrochemical activity of the material, but also unexpectedly enhances the thermal stability and durability of the material. These significant technical effects exceed the expectations of traditional preparation methods, fully proving the non-obviousness and innovation of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0041] Figure 1 The SEM and XRD images of the high entropy spinel oxide prepared at different calcination temperatures of the present invention;
[0042] Among them, (a)-(f) are SEM images, (a) 0°C (Comparative Example 1), (b) 400°C (Example 3), (c) 500°C (Example 4), (d) 600°C (Example 5), (e) 700°C (Example 6), (f) 900°C (Example 7), and (g) are XRD images;
[0043] Figure 2 The SEM and XRD images of the high entropy spinel oxide prepared under different hydrothermal conditions at 500° C. in Example 4 of the present invention; (a) microwave hydrothermal, (b) conventional hydrothermal, and (c) XRD image;
[0044] Figure 3For Example 1, Example 2 and Example 7 of the present invention, at 900° C., (a)-(c) SEM images of the precipitants are 1:4, 1:5, and 1:6, respectively, and (d) XRD images of the precipitants are 1:4, 1:5, and 1:6, respectively;
[0045] Figure 4 The figures are LSV diagrams of high entropy spinel oxides prepared under different hydrothermal conditions; wherein, (a) is the LSV diagram at different heat treatment temperatures (Examples 3-7); (b) is the LSV diagram of conventional-microwave comparison at 500°C; (c) is the LSV diagram at different precipitant contents (different precipitant contents correspond to Examples 1, 2 and 7, respectively).
[0046] Figure 5 The stability diagrams of hydrogen evolution (right) and oxygen evolution (left) of Example 4 of the present invention at 500° C. and 1:6 are shown. DETAILED DESCRIPTION
[0047] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0048] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0049] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0050] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0051] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0052] The invention discloses a method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by a microwave hydrothermal method, comprising the following steps:
[0053] Dissolve iron nitrate, cobalt nitrate, nickel nitrate, chromium nitrate, zinc nitrate and copper nitrate in deionized water respectively and stir them thoroughly to obtain a mixed solution of metal salts; introduce urea as a precipitant into the mixed solution, and then transfer it to a microwave synthesizer for hydrothermal reaction (synthesis conditions of the microwave synthesizer: microwave rated output power is 400W; microwave operating frequency: 2450MHz); after the reaction is completed, cool to room temperature to form a precipitate, wash it with ethanol and deionized water three times in sequence, centrifuge it at 8000rpm for 3min, and then dry it at 60℃ for 10h, and anneal the powder in air at 300-900℃ for 0.5-5h to obtain a high entropy spinel oxide material.
[0054] In some preferred embodiments, the concentration of each metal nitrate in the mixed solution of six metal nitrate salts is 0.01-0.06 mol / L to ensure the normal progress of the hydrothermal reaction.
[0055] In some preferred embodiments, the precipitant is urea, and the molar ratio of the precipitant to all metal ions in the metal nitrate is (3-6): 1. The role of adding the precipitant is to adjust the pH of the solution and provide a uniform precipitation environment, so that the metal ions form uniform and fine precipitation particles. The amount of precipitant added has a significant effect on the sample morphology. When the amount is appropriate, uniform and fine particles can be formed, but an excessive amount may cause the precipitate to agglomerate or form irregular large particles, while too little may cause incomplete precipitation or uneven particle sizes. Therefore, accurately controlling the amount of precipitant added is the key to obtaining an ideal sample morphology.
[0056] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0057] The raw materials used in the present invention are all purchased from the market.
[0058] The technical solution of the present invention is further illustrated by the following embodiments.
[0059] Example 1
[0060] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0061] 1. Weigh according to the raw material ratio and set aside
[0062] Weigh Fe(NO3)3·9H2O (0.001 mol), Co(NO3)2·6H2O (0.001 mol), Ni(NO3)2·6H2O (0.001 mol), Cr(NO3)2·9H2O (0.001 mol), Zn(NO3)2·6H2O (0.001 mol), and Cu(NO3)2·3H2O (0.001 mol), and the molar ratio of urea to the total amount of metal ions is 4:1;
[0063] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution to obtain a mixed solution;
[0064] 3. The mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400 W; microwave operating frequency: 2450 MHz; hydrothermal temperature: 100°C; synthesis time: 2 h) for reaction. After the reaction was completed, the microwave reactor was cooled to room temperature and the liquid was removed under reduced pressure; then, the liquid was centrifuged to precipitate solid matter; the precipitate was washed with ethanol and deionized water three times in sequence and centrifuged at 8000 rpm for 3 min;
[0065] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 900°C for 2 hours to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0066] Figure 1 The SEM and XRD images of the high entropy spinel oxide prepared at different calcination temperatures of the present invention;
[0067] Among them, (a)-(f) are SEM images, (a) 0℃ (Comparative Example 1), (b) 400℃ (Example 3), (c) 500℃ (Example 4), (d) 600℃ (Example 5), (e) 700℃ (Example 6), (f) 900℃ (Example 7), and (g) are XRD images; it can be seen from the XRD image that the main peak positions of the five spinels are at 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, respectively belonging to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes; it can be seen from the SEM image that the calcination temperature affects the porosity and nanodiameter of the sample. Too low a temperature may lead to incomplete decomposition of the raw materials, forming an amorphous or partially crystallized structure. Too high a temperature may lead to excessive sintering of the sample, a reduction in diameter, and may also cause destruction or phase change of the spinel structure, affecting its performance. Therefore, controlling the calcination temperature is a key step in the preparation of spinel nanoparticles.
[0068] Figure 2 The SEM and XRD images of the high entropy spinel oxide prepared under different hydrothermal conditions at 500°C in Example 4 of the present invention; (a) microwave hydrothermal, (b) conventional hydrothermal (the difference from Example 4 is that microwave hydrothermal is replaced by conventional hydrothermal), (c) is the XRD image; Figure 2 As can be seen from (a), the microwave hydrothermal method formed small round nanoparticles with regular morphology, large porosity, and no agglomeration. Figure 2 It can be seen from (b) that the grain size obtained by conventional hydrothermal method is larger, the pore structure is less, and there are more agglomeration phenomena and crystal defects; Figure 2 (c) It can be seen from the XRD patterns under different hydrothermal conditions that the high-entropy spinel prepared by microwave hydrothermal method usually shows sharper and more symmetrical diffraction peaks in the XRD spectrum, indicating that the crystal structure is more complete and ordered, while the spinel prepared by conventional hydrothermal method may show broader and less symmetrical diffraction peaks, reflecting that its crystal structure is less ordered.
[0069] Figure 4The figures are LSV diagrams of high entropy spinel oxides prepared under different hydrothermal conditions; wherein, (a) is the LSV diagram at different heat treatment temperatures (Examples 3-7); (b) is the LSV diagram of conventional-microwave (Example 4) comparison at 500°C; (c) is the LSV diagram under different precipitant contents (corresponding to Example 1, Example 2 and Example 7). In order to reveal the effect of high entropy spinel oxides under different hydrothermal conditions on the electrocatalytic activity of the material, the present invention uses a standard three-electrode to measure the HER performance of (FeCoNiCrZnCu)3O4. The HER catalytic activity of the HEO / NF electrode was analyzed in 1M KOH solution. Figure 4 As shown in (b), it was found that the sample prepared under microwave hydrothermal conditions had a -2 At 138 mV, the HER performance of microwave hydrothermal (138 mV) is significantly better than that of samples prepared under conventional hydrothermal conditions (161 mV).
[0070] Example 2
[0071] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0072] 1. Weigh and set aside according to the raw material ratio;
[0073] Weigh Fe(NO3)3·9H2O (0.002 mol), Co(NO3)2·6H2O (0.002 mol), Ni(NO3)2·6H2O (0.002 mol), Cr(NO3)2·9H2O (0.002 mol), Zn(NO3)2·6H2O (0.002 mol), and Cu(NO3)2·3H2O (0.002 mol) as raw materials, and the ratio of urea to metal ions is (5:1);
[0074] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution;
[0075] 3. Subsequently, the mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400 W; microwave operating frequency: 2450 MHz; hydrothermal temperature: 100°C; synthesis time: 2 h). After the reaction was completed, the microwave reactor was cooled to room temperature, and the liquid was removed under reduced pressure. Then, the liquid was centrifuged to precipitate solid matter. The precipitate was washed three times with ethanol and deionized water in sequence, and centrifuged at 8000 rpm for 3 min.
[0076] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 900°C for 2 hours to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0077] like Figure 3 The XRD diagram of 1:5 is that the ratio of metal ions to urea content in Example 2 is 1:5 at 900°C. From the XRD diagram, it can be seen that the main peak positions of the five spinels are 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, which belong to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. Figure 3 As can be seen from the SEM in (b), under this condition, grains with various morphologies were successfully synthesized. These grains are arranged tightly and orderly and are evenly distributed throughout the structure, showing good crystal growth characteristics. Figure 4 FCNCZC-5:1 in (a) is the LSV curve of the sample at 900℃.
[0078] Example 3
[0079] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0080] 1. Weigh and set aside according to the raw material ratio;
[0081] Fe(NO3)3·9H2O(0.002mol), Co(NO3)2·6H2O(0.002mol), Ni(NO3)2·6H2O(0.002mol), Cr(NO3)2·9H2O(0.002mol), Zn(NO3)2·6H2O(0.002mol), and Cu(NO3)2·3H2O(0.002mol) were weighed as raw materials, and the ratio of urea to metal ions was (6:1);
[0082] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution;
[0083] 3. Subsequently, the mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400 W; microwave operating frequency: 2450 MHz; hydrothermal temperature: 100°C; synthesis time: 1 h). After the reaction was completed, the microwave reactor was cooled to room temperature, and the liquid was removed under reduced pressure. Then, the liquid was centrifuged to precipitate solid matter. The precipitate was washed three times with ethanol and deionized water in sequence, and centrifuged at 8000 rpm for 3 min.
[0084] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 400°C for 2 hours to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0085] like Figure 1 The XRD pattern at 400°C in (g) shows that the ratio of metal ions to urea content in Example 3 at 400°C is 1:6. From the XRD pattern, it can be seen that the main peak positions of the five spinels are 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, which belong to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. Figure 1 From the SEM in (b), it can be seen that the sample synthesized under this condition has some holes. Figure 4 FCNCZC-400℃ in (a) is the LSV curve of the sample at 400℃.
[0086] Example 4
[0087] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0088] 1. Weigh and set aside according to the raw material ratio;
[0089] Fe(NO3)3·9H2O(0.003mol), Co(NO3)2·6H2O(0.003mol), Ni(NO3)2·6H2O(0.003mol), Cr(NO3)2·9H2O(0.003mol), Zn(NO3)2·6H2O(0.003mol), and Cu(NO3)2·3H2O(0.003mol) were weighed as raw materials, and the ratio of urea to metal ions was (6:1);
[0090] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution;
[0091] 3. Then, the mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400W; microwave operating frequency: 2450MHz; hydrothermal temperature: 100℃; synthesis time: 1h). After the reaction was completed, the microwave reactor was cooled to room temperature, and the liquid was removed under reduced pressure. Then, the liquid was centrifuged to precipitate solid matter. The formed precipitate was washed with ethanol and deionized water three times in sequence, and centrifuged at 8000rpm for 3min;
[0092] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 500°C for 2 hours to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0093] like Figure 1 The XRD pattern at 500°C in (g) shows that the ratio of metal ions to urea content in Example 4 at 500°C is 1:6. From the XRD pattern, it can be seen that the main peak positions of the five spinels are 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, which belong to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. Figure 1 From the SEM in (c), it can be seen that the sample synthesized under this condition has some holes. Figure 4 FCNCZC-500℃ in (a) is the LSV curve of the sample at 500℃.
[0094] Example 5
[0095] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0096] 1. Weigh and set aside according to the raw material ratio;
[0097] Fe(NO3)3·9H2O(0.004mol), Co(NO3)2·6H2O(0.004mol), Ni(NO3)2·6H2O(0.004mol), Cr(NO3)2·9H2O(0.004mol), Zn(NO3)2·6H2O(0.004mol), and Cu(NO3)2·3H2O(0.004mol) were weighed as raw materials, and the ratio of urea to metal ions was (6:1);
[0098] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution;
[0099] 3. Then, the mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400W; microwave operating frequency: 2450MHz; hydrothermal temperature: 160℃; synthesis time: 1h). After the reaction was completed, the microwave reactor was cooled to room temperature and the liquid was removed under reduced pressure. Next, the liquid was centrifuged to precipitate solid matter. The precipitate was washed three times with ethanol and deionized water in sequence and centrifuged at 8000rpm for 3min.
[0100] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 600°C for 2 hours to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0101] like Figure 1 The XRD pattern at 600°C in (g) shows that the ratio of metal ions to urea content in Example 5 at 600°C is 1:6. From the XRD pattern, it can be seen that the main peak positions of the five spinels are at 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, which belong to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. Figure 1 From the SEM in (d), it can be seen that the sample synthesized under this condition has some holes. Figure 4 FCNCZC-600℃ in (a) is the LSV curve of the sample at 600℃.
[0102] Example 6
[0103] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0104] 1. Weigh and set aside according to the raw material ratio;
[0105] Fe(NO3)3·9H2O (0.005 mol), Co(NO3)2·6H2O (0.005 mol), Ni(NO3)2·6H2O (0.005 mol), Cr(NO3)2·9H2O (0.005 mol), Zn(NO3)2·6H2O (0.005 mol), and Cu(NO3)2·3H2O (0.005 mol) were weighed as raw materials, and the ratio of urea to metal ions was (6:1);
[0106] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution;
[0107] 3. Then, the mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400W; microwave operating frequency: 2450MHz; hydrothermal temperature: 100℃; synthesis time: 1h). After the reaction was completed, the microwave reactor was cooled to room temperature and the liquid was removed under reduced pressure. Next, the liquid was centrifuged to precipitate solid matter. The precipitate was washed three times with ethanol and deionized water in sequence and centrifuged at 8000rpm for 3min.
[0108] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 700°C for 1 hour to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0109] like Figure 1 The XRD pattern at 700°C in (g) shows that the ratio of metal ions to urea content in Example 6 at 700°C is 1:6. From the XRD pattern, it can be seen that the main peak positions of the five spinels are 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, which belong to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. Figure 1 From the SEM in (e), it can be seen that the sample synthesized under this condition has some holes. Figure 4 FCNCZC-700℃ in (a) is the LSV curve of the sample at 700℃.
[0110] Example 7
[0111] A method for preparing a high entropy spinel oxide material (FeCoNiCrZnCu)3O4 by microwave hydrothermal method, the specific steps are as follows:
[0112] 1. Weigh and set aside according to the raw material ratio;
[0113] Fe(NO3)3·9H2O (0.005 mol), Co(NO3)2·6H2O (0.005 mol), Ni(NO3)2·6H2O (0.005 mol), Cr(NO3)2·9H2O (0.005 mol), Zn(NO3)2·6H2O (0.005 mol), and Cu(NO3)2·3H2O (0.005 mol) were weighed as raw materials, and the ratio of urea to metal ions was (6:1);
[0114] 2. Dissolve the above six nitrates in 100 mL of water and stir evenly. After the six metal elements are completely mixed, continue to add urea to the solution;
[0115] 3. Then, the mixed solution was transferred to a microwave synthesizer (microwave rated output power: 400W; microwave operating frequency: 2450MHz; hydrothermal temperature: 100℃; synthesis time: 1h). After the reaction was completed, the microwave reactor was cooled to room temperature and the liquid was removed under reduced pressure. Next, the liquid was centrifuged to precipitate solid matter. The precipitate was washed three times with ethanol and deionized water in sequence and centrifuged at 8000rpm for 3min.
[0116] 4. Then, the powder was dried at 60°C for 10 hours, and the powder was annealed in air at 900°C for 1 hour to obtain a high entropy spinel oxide material. During the entire calcination process, the heating rate was controlled at 10°C / min, and the temperature was lowered as the furnace cooled.
[0117] like Figure 1 The XRD pattern at 900°C in (g) shows that the ratio of metal ions to urea content in Example 7 at 900°C is 1:6. From the XRD pattern, it can be seen that the main peak positions of the five spinels are at 18.453°, 30.357°, 35.760°, 37.408°, 43.466°, 53.938°, 57.503°, and 63.156°, which belong to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. Figure 1 From the SEM in (f), it can be seen that the sample synthesized under this condition has some holes. Figure 4 FCNCZC-900℃ in (a) is the LSV curve of the sample at 900℃.
[0118] Comparative Example 1
[0119] The difference from Example 3 is that the annealing temperature in step 4 is 0°C.
[0120] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing high entropy spinel oxide materials using microwave hydrothermal method, characterized in that: The following steps are involved: Dissolve six metal sources, namely iron, cobalt, nickel, chromium, zinc and copper, in water in equal moles of metal ions, and stir evenly to obtain a mixed solution; A precipitant is added to the mixed solution, and then microwave hydrothermal, cooling, washing, centrifugation, drying and calcination are performed in sequence to obtain a high entropy spinel oxide material (FeCoNiCrZnCu)3O4.
2. The method for preparing high entropy spinel oxide materials by microwave hydrothermal method according to claim 1, characterized in that: The metal source is a metal nitrate.
3. The method for preparing high entropy spinel oxide material by microwave hydrothermal method according to claim 2, characterized in that: In the mixed solution, the concentration of each metal ion is 0.01-0.06 mol / L.
4. The method for preparing high entropy spinel oxide materials by microwave hydrothermal method according to claim 1, characterized in that: The precipitant includes one or two of disodium ethylenediaminetetraacetate, ammonium fluoride, glucose, ammonia water or urea.
5. The method for preparing high entropy spinel oxide material by microwave hydrothermal method according to claim 4, characterized in that: The molar ratio of the precipitant to the total amount of metal ions in the mixed solution is (3-6):
1.
6. The method for preparing high entropy spinel oxide material by microwave hydrothermal method according to claim 1, characterized in that: The parameter conditions in the microwave hydrothermal process are: The rated output power of the microwave is 400W, the microwave operating frequency is 2450MHz, the microwave hydrothermal temperature is 100-160℃, and the insulation time is 0.5-6h.
7. The method for preparing high entropy spinel oxide material by microwave hydrothermal method according to claim 1, characterized in that: The drying process is: drying at 60° C. for 10 hours.
8. The method for preparing high entropy spinel oxide material by microwave hydrothermal method according to claim 1, characterized in that: The calcination process is: The temperature is raised to 300-900°C at a heating rate of 2-10°C / min, and then maintained at this temperature for 0.5-5h.
9. A high entropy spinel oxide material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the high entropy spinel oxide material as claimed in claim 9 in the field of catalytic water electrolysis.
Citation Information
Patent Citations
Preparation method of high-entropy oxide with good infrared radiation performance
CN113387684A
Method for preparing high-entropy oxide material (MAlFeCuMg)3O4 by hydrothermal method
CN113461415A
Preparation method of high-entropy epitaxial self-energized perovskite ferroelectric film
CN118574482A
A system for establishing a digital interconnection between vessels for collection of micro-plastics in a secured way
KR1020240131887A
Cited By
Spherical hollow multi-layer high-entropy metal oxide as well as preparation method and application thereof
CN120998695A
Metal oxide as well as preparation method and application thereof
CN122144799A
Hydro-thermal synthesis rod-like powder sintered magnesium aluminate spinel transparent ceramic and preparation method thereof
CN122325216A